THE JOURNEY OF ISRA' AND MI'RAJ IN QURAN AND SCIENCE PERSPECTIVE - Rahmati, Rahmati (UIN Ar-Raniry, 2017)
Isra Mi'raj raises many riddles from the scholars and scientists. It also raises many doubts among Muslims about the validity. Based on that journey, many questions arise whether the physical and the spirit of Muhammad as a whole or just soul which is tripped by God. The speed of light which is expressed as the highest speed in science is not enough to make that far trip in a short time. This paper discuss about the information that leads to the new indication, even though the truth cannot be ascertained. This paper used the zero Celvin theory to interpret Surah Al-Isra verse 1.